Hydrogeochemical characterization of groundwater using water quality index and multivariate statistical analysis in Binji town and environs, Sokoto basin, Northwestern Nigeria - Ibrahim Mohammed Abdullahi; Lawali Abubakar; Garba Saidu; Hassan Yusuf (Applied Water Science)
Abstract The hydrogeochemistry of groundwater from Binji community and surroundings was assessed. The main aim of the study was to characterize the groundwater in the study area through the application of indexing and statistical methods. Measured PH revealed 12 samples to be acidic and 15 samples to be alkaline with majority of the samples from dug wells having PH that indicates alkalinity. The concentration of analyzed chemical parameters in sampled water revealed the dominance of Ca over other metals detected in the groundwater, with the dominance given in the order Ca˃ Mg ˃ Na ˃ K. The anions were dominated by HCO3 in the order HCO3 ˃ Cl ˃ SO4 ˃ CO3. Ca ion exceeded the Nigerian standard for drinking water quality (NSDWQ) and the World Health Organization (WHO) set limits in one sample, Mg in 14 samples while K exceeded in four samples. HCO3 exceeded both standards in 21 samples; Total dissolved solids and electrical conductivity were above the maximum permissible limits in four samples. Five different water types were identified in the area with Ca + Mg- HCO3 dominating other types. Computed water quality index (WQI) for drinking water gave values that are within the range of 18–77.5 indicating the groundwater to be within the excellent and good classes of suitable drinking water quality. Irrigation water quality index revealed the groundwater to be suitable except for the magnesium hazard. Correlation analysis gave a moderate positive correlation that ranges from 0.632 to 0.659 between total hardness, Mg and HCO3, and that between Mg and HCO3 indicates the contribution of these elements to the hardness of water. Principal component analysis gave six components with a total variance of 76.19% with eigenvalues above 1 with the range of 1.52 – 4.26. Cluster analysis performed on the hydrogeochemical parameters demarcated four clusters based on the sources, hydrogeochemical environment, and reactions between chemical variables. Correlation between many chemical species revealed formation under a common hydrogeochemical environment. Gibb’s plot showed the sources of chemical constituents of groundwater to be dominated by precipitation source. The groundwater of the area is hard water that is fresh and safe for drinking and other domestic uses.